An Experimental Study On Stabilization Of Pekan Clay Using Polyethylene And Polypropylene - Azhani, Zukri; Nazir, Ramli; Fatin Nabilah, Mender (AIP Publishing, 2017)
Many countries are expressing concern over the growing issues of polyethylene terephthalate (PET) bottles and polypropylene (PP) products made by the household sector. The rapid increase in the generation of plastic waste all around the world is due to the economic development and population growth. PP is the world's second-most widely produced synthetic plastic, after polyethylene. Statistics show that nearly 50% of the municipal solid waste in Malaysia comes from the institutional, industrial, residential, and construction waste. This paper presents the results of an investigation on the utilisation of fibres as products of PET bottles and PP products in order to improve the engineering properties of clay soil in Pekan. The soil samples were taken from Kampung Tanjung Medang, Pekan, Pahang. The basic properties of the clay soil were determined as follows; optimum moisture content: 32.5%, maximum dry density: 13.43 kN/m3, specific gravity: 2.51, liquid limit: 74.67%, plastic limit: 45.98%, and plasticity index: 28.69%. This investigation concentrates on the shear strength of the reinforced clay soils with PET and PP in random orientation. The reinforced soil samples were subjected to unconfined compression test (UCT) to differentiate their shear strength with that of the unreinforced soil. The tests found that the waste fibres (PET and PP) improved the strength properties of the Pekan clayey soils. The unconfined compressive strength (UCS) value increased with the increasing percentage of PET fibre and reached the optimum content at 10% reinforcement, where it showed the highest improvement of 365 kN/m2 from 325 kN/m2 and depleted when the optimum content reached 20% reinforcement. For PP fibre, the reinforced soil showed the highest UCS at 20% reinforcement with the improvement of 367 kN/m2. The study concluded that the PET and PP fibres can be utilised successfully as reinforcement materials for the stabilisation of clayey soils. The use of these waste compounds as alternative materials for clay soil stabilisation is reasonable and cost effective since they are constantly available.